The gender communication handbook : conquering conversational collisions between men and women - Nelson, Audrey, 1948- (Pfeiffer essential resources for training and HR professionals., 2012)
"Men and women exhibit distinct, innate, and acculturated sex differences in their verbal and nonverbal communication styles. In the work environment, the difficulties and misunderstandings generated by these differences not only reduce productivity and efficiency but also lower morale. In this book, the authors show through empirical research and extensive anecdotal evidence--garnered from fifty years of combined corporate work experience, research, gender seminars, coaching and consulting--the specific verbal and nonverbal behaviors men and women employ that define our sex roles' expectations yet paradoxically often ultimately result in barriers to effective inter-gender communication"--